The Influence of Fraud Hexagon Theory on Fraud in Fund Management at LPDs: A Case Study of LPDs in Tabanan Regency - Ni Komang Urip Krisna Dewi; Ni Putu Erviani Astari; Anak Agung Ayu Intan Wulandari; Irene Ipal Parinding (CV Edujavare Publishing, 2026)
This study aims to analyze the influence of Fraud Hexagon Theory and governance weaknesses on fraud in fund management at LPDs in Tabanan Regency. The research uses a quantitative approach with a case study design involving 32 LPDs and 120 respondents consisting of managers, treasurers, and supervisory staff. Data were collected through structured questionnaires using a Likert scale and supported by financial reports and audit documents. The data analysis technique employed multiple linear regression analysis along with classical assumption tests to ensure model validity. The results show that all dimensions of the Fraud Hexagon Theory—pressure, opportunity, rationalization, capability, arrogance, and collusion—have a significant influence on fraud occurrence, with opportunity and collusion being the most dominant factors. In addition, governance weaknesses such as poor internal control systems, weak segregation of duties, limited transparency, and inadequate external supervision significantly increase fraud risk in LPD fund management. Overall, the study concludes that fraud in LPDs is driven by both behavioral and structural factors, indicating that effective fraud prevention requires strengthening governance systems and controlling multidimensional fraud risks simultaneously.